2008
DOI: 10.1108/09653560810855919
|View full text |Cite
|
Sign up to set email alerts
|

Flood hazard mapping in developing countries: problems and prospects

Abstract: PurposeThis paper aims to describe the major causes of massive destruction due to floods in developing countries and to elaborate the usefulness of flood hazard maps under the framework of community‐based flood management.Design/methodology/approachThis paper elaborates the usefulness of flood hazard maps and their application.FindingsIt is a clear perception that flood risk management cannot be treated in isolation – rather it should be a part of community development. In this context, it is essential to buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 3 publications
0
33
0
2
Order By: Relevance
“…It is natural that countries with a better GDP allocate more of their budget for water-related disaster management ( Figure 2). In developing nations, disaster mitigation structures are often dysfunctional; in some cases, there are no accurate data on such structures as EWSs, and no hazard maps (Osti et al, 2008). In 2009, during Typhoon Ketsana in Manila, the clogging of channels and drainage systems contributed to the inundation resulting in life loss and property damage (ADB, 2011); this could have been attenuated to some extent had there been proper planning and budget for maintenance.…”
Section: Governance Indicatorsmentioning
confidence: 98%
“…It is natural that countries with a better GDP allocate more of their budget for water-related disaster management ( Figure 2). In developing nations, disaster mitigation structures are often dysfunctional; in some cases, there are no accurate data on such structures as EWSs, and no hazard maps (Osti et al, 2008). In 2009, during Typhoon Ketsana in Manila, the clogging of channels and drainage systems contributed to the inundation resulting in life loss and property damage (ADB, 2011); this could have been attenuated to some extent had there been proper planning and budget for maintenance.…”
Section: Governance Indicatorsmentioning
confidence: 98%
“…to the local residents, is indispensable for emergency response and for long-term flood disaster management (Osti et al 2008). In this study, a flood hazard map was prepared using the inundation status, which was found from hydrologic simulation.…”
Section: Flood Hazard Mappingmentioning
confidence: 99%
“…Several studies (Green 1998;Faisal et al 1999;Osti et al 2008;Vojinovic & Teeffelen 2007) have stretched the need for both structural and non-structural measures to manage floods. The importance and need for non-structural measures is specially realized when structural measures fail to provide effective results in the face of flood disasters.…”
Section: Non-structural Measures and Flood Hazard Mappingmentioning
confidence: 99%
“…Both structural and unstructural measures should be technically sound, environment friendly, socially accepted and cost-effective in order to be part of the communitybased planning and implementation (Osti et al 2008). …”
Section: Non-structural Measures and Flood Hazard Mappingmentioning
confidence: 99%